Effectiveness of aerobic and resistance training on the motor symptoms in Parkinson's disease: Systematic review and network meta-analysis - Zhou, Xiao; Zhao, Peng; Guo, Xuanhui; Wang, Jialin; Wang, Ruirui (Frontiers in Aging Neuroscience, 2022)
Background/Objectives: Aerobic and resistance training are common complementary therapies to improve motor symptoms in people with Parkinson's disease (PD), and there is still a lack of advice on which intensity and period of aerobic or resistance training is more appropriate for people with PD. Therefore, a network meta analysis was conducted to assess the comparative efficacy of aerobic and resistance training of different intensities and cycles on motor symptoms in patients with Parkinson's disease. Methods: Based on several biomedical databases, a search strategy system was conducted to retrieve randomized controlled trials (RCTs) without language restrictions. A network meta-analysis with a frequentist approach was conducted to estimate the efficacy and probability rankings of aerobic and resistance training on Parkinson’s patients. What’s more, a range of analyses and assessments, such as routine meta-analyses and risk of bias, were performed as well. Results: Twenty trials with 719 patients evaluating eighteen different therapies were identified. Through the Unified Parkinson’s Disease Motor Rating Scale, (UPDRS III); 6-minute walk test, (6MWT); 10-meter walk test, (TWM); and time up and go (TUG) and Quality of Life Scale-39 (PDQ-39), to explore the effects of different intensity resistance and aerobic exercise on PD. As a result, short period high intensity resistance movement (standard mean difference (SMD) = −0.95, 95% con-fidence interval (CI) –1.68 to −0.22) had significantly decreased the Unified Parkinson’s Disease Mo-tor Rating Scale (UPDRS III). Short period high intensity resistance exercise showed similar superior-ity in other indices; also, aerobic and resistance training of different cycle intensities produced some efficacy in PD patients, both in direct and indirect comparisons. Conclusion: For patients with moderate to mild Parkinson's symptoms, short periods high intensity resistance training may provide complementary therapy for PD, and aerobic or resistance training of varying intensity and periodicity may be recommended as exercise prescription for PD patients. How-ever, more large scale and high quality clinical trials are needed to confirm the effectiveness of this exercise therapy in the future.